Surface enhanced Raman spectroscopy-detection of the uptake of mannose-modified nanoparticles by macrophages in vitro: A model for detection of vulnerable atherosclerotic plaques - Dugandzic, Vera; Drikermann, Denis; Ryabchykov, Oleg; Undisz, Andreas; Vilotijevic, Ivan; Lorkowski, Stefan; Bocklitz, Thomas W.; Matthaeus, Christian; Weber, Karina; Cialla-May, Dana; Popp, Jürgen (Journal of Biophotonics, 2018)
Atherosclerosis is a process of thickening and stiffening of the arterial walls through the accumulation of lipids and fibrotic material, as a consequence of aging and unhealthy life style. However, not all arterial plaques lead to complications, which can lead to life-threatening events such as stroke and myocardial infarction. Diagnosis of the disease in early stages and identification of unstable atherosclerotic plaques are still challenging. It has been shown that the development of atherosclerotic plaques is an inflammatory process, where the accumulation of macrophages in the arterial walls is immanent in the early as well as late stages of the disease. We present a novel surface enhanced Raman spectroscopy (SERS)-based strategy for the detection of early stage atherosclerosis, based on the uptake of tagged gold nanoparticles by macrophages and subsequent detection by means of SERS. The results presented here provide a basis for future in vivo studies in animal models.The workflow of tracing the SERS-active nanoparticle uptake by macrophages employing confocal Raman imaging.
CRIS-Team Scopus Importer:2023-04-20
Keywords: atherosclerosis; gold nanoparticles; macrophages; mannose; SERS; silica coating